Pengolahan Sampah Plastik Berbasis Ekonomi Sirkular Bagi Masyarakat Kelurahan Limo Menuju Penerapan Kampung Caraka Kota Depok - Martana, Budhi; Pradana, Sigit; Fahrudin, Fahrudin; Hernawati, Erna; Sari, Retna; Septin, Althearae Nira (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
This activity aims to support the implementation of the Depok City Caraka (Smart Family Friendly) Village Program which is implemented at the Rukun Warga (RW) level in order to realize Family Resilience and Smart Villages. The target of the activity is focused on initiating circular economy-based plastic waste processing. The methods used include outreach activities, training, application of production technology and practices for making plastic waste recycling products with a circular economy concept. The result of this activity is the creation of a collaboration, specifically between the Limo Village Government, Limo District, Depok City and the Jakarta